African Red Slip Ware in Lydian Tripolis - Duman, Bahadır (Rei Cretariae Romanae Fautorum Acta, 2017)
The African Red Slip Ware presented in this study originates from the excavations of Tripolis. The city is located within the municipal boundaries of Yenicekent, Buldan, Denizli, Turkey. In the ancient period, it was significantly to be at the convergence of the Lydian, Carian, and Phrygian territories. The African Red Slip Ware was evaluated in this study on the basis of information obtained from both the surveys and the excavations in one of the border towns in the south-eastern region of Lydia. Traces of life in and around the city date from 3 500 BC. Construction as a polis with a grid street plan began in the Hellenistic period. During the Roman period, Tripolis was similar to the neighboring cities such as Hierapolis, Laodicea, and Blaundos in terms of urban planning and architectural construction.